2014
DOI: 10.1177/0020764014535755
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of non-suicidal self-injurious behaviours among college students in India

Abstract: The findings underscore the need to increase the awareness and understanding of NSSIs and to plan targeted interventions among college youth.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
53
2
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(60 citation statements)
references
References 69 publications
4
53
2
1
Order By: Relevance
“…More detailed results on the characteristics of self-injury in this sample are available in a previous publication. [18]…”
Section: Methodsmentioning
confidence: 99%
“…More detailed results on the characteristics of self-injury in this sample are available in a previous publication. [18]…”
Section: Methodsmentioning
confidence: 99%
“…Avoidance only enhances the likelihood of high stress, nervousness, and anxiety, given that uncertainty manifests as a continuous threat that calls for resolution (Hofstede, 1980). An Indian study found that the most two common reasons for DSH among college students was compromise of the need "to feel relaxed (41.8%)" and "in control (41.1%)" (Kharsati and Bhola, 2015). Self-harming is an unhealthy adaptation to uncertainty stress, even if it helps relieve the potential negative effect of stress associated with a perceived loss or losing of self-control (Atienza et al, 2001).…”
Section: Uncertainty Stress and Dshmentioning
confidence: 99%
“…In recent years, DSH has become more prevalent among adolescents and young adults, and consequently a more prominent research topic (Kerr et al, 2010). Prevalence of DSH appears high among college students (Kharsati and Bhola, 2015;Li and Meng, 2014). A plausible explanation is that the students are in emerging adulthood (ages stressors (Arria et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, disclosure of NSSI was low among both sexes, because only 8.9% disclosed their self-injuries to a mental health professional. Kharsati and Bhola (2014) found that the most common method of NSSI was self-hitting (15.2%), followed by cutting or carving skin (13.2%). Self-efficacy has been found to be related to depressive and anxiety symptoms and in one study to mediate the relation of stressful life events with depression and anxiety symptoms (Maciejewski, Prigerson, & Mazure, 2000;Muris, 2002).…”
Section: Introductionmentioning
confidence: 99%